Utilização do primeiro ciclo ovulatório da estação reprodutiva para produção de embriões em éguas sob condições tropicais - Peres, Karen Regina; Landim-Alvarenga, Fernanda da Cruz [UNESP]; Alvarenga, Marco Antonio [UNESP] (My University, 2006)
The efficacy of the first ovulation of the breeding season was determined through the response of first pre-ovulatory follicle of the breeding season to hCG, embryo recovery rate, viability of recovered embryos, serum concentrations of progesterone, and response of first CL to PGF 2α. Thirteenth mares that were in vernal transition were accompanied until the first pre-ovulatory follicle was detected. At this moment, the ovulation was induced with 2,500 IU hCG (IV) and the mares were inseminated every other day until ovulation. Seven days after the ovulation, embryo recovery was performed and the progesterone concentration was determined. After detection of the first pre-ovulatory follicle of breeding season with ≥ 25mm, it took 14.92 ± 10.80 days for the follicle to reach the preovulatory size and 18.00 ± 11.08 days to ovulation. After administration of hCG, 11/13 mares ovulated in 48 hours. These follicles growth 2.19 ± 0.86 mm/day on average. Nine of 13 mares (69.2%) produced embryos and all were considered viable after morfological evaluation and fluorescence exams. The CL appeared competent producing 7.39 ± 2.11 ng/ml P 4 on average, and responding to PGF 2α. According to these results the first ovulatory cycle of the year can be utilized to produce viable embryos.
Utilization of the first ovulatory cycle of seasonal breeding for embryo production in mares in tropical conditions
Keywords: Embryo; Mare; Ovulation; Progesterone